The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/pfi.20183
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of a pilot Geospatial Technology Apprenticeship Program for the Department of Labor

Abstract: The Geospatial Technology Apprenticeship Program (GTAP) pilot was designed as a replicable and sustainable program to enhance workforce skills in geospatial technologies to best leverage a $30 billion market potential. The purpose of evaluating GTAP was to ensure that investment in this high‐growth industry was adding value. Findings from this evaluation showed that investments in geospatial technology competency development have the potential for high‐systemic payoffs and sustained economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…As several of the papers reported on one or more of these trades, most of what we know about RA in the United States is from the skilled trades context (i.e., RA in industrial and construction trades such as welding, ironworking, plumbing, and carpentry). Today, the RA model is also expanding into many new industries, such as tech and STEM fields (Gaudet et al, 2010; Kuehn & Jones, 2018; Kuehn et al, 2019; Sharp & Dvorkin, 2018), the insurance industry (Cheney, 2017), transit maintenance occupations (Glover et al, 2007), and early childhood education (Copeman Petig et al, 2019; Uttley & Horm, 2008; Workman, 2019). Hecker and Kuehn (2019) encouraged the expansion of RA within the U.S. prison system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As several of the papers reported on one or more of these trades, most of what we know about RA in the United States is from the skilled trades context (i.e., RA in industrial and construction trades such as welding, ironworking, plumbing, and carpentry). Today, the RA model is also expanding into many new industries, such as tech and STEM fields (Gaudet et al, 2010; Kuehn & Jones, 2018; Kuehn et al, 2019; Sharp & Dvorkin, 2018), the insurance industry (Cheney, 2017), transit maintenance occupations (Glover et al, 2007), and early childhood education (Copeman Petig et al, 2019; Uttley & Horm, 2008; Workman, 2019). Hecker and Kuehn (2019) encouraged the expansion of RA within the U.S. prison system.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the reviewed studies do provide limited insights on what promotes or creates conditions for learning, but the studies are so distinct from one another in context, learning population, and purpose that it is difficult to draw conclusions for RA design. For example, in their analysis of benefits and costs of RA for businesses, Gaudet et al (2010) evaluated a geospatial technology apprenticeship program, concluding that apprentices passed skills tests and perceived course work as relevant, suggesting some learning occurred, but the authors did not venture guesses as to why. In a small, quantitative study of electrical industry apprentices and instructors, one researcher found evidence that respondents reported a higher occupational work ethic than other study contexts in which their instrument had been used, but the author did not explain why or how (Hatcher, 1995).…”
Section: Theme 1: Expansionmentioning
confidence: 99%
“…Competency models that integrate technical aspects, business skills, analytical, and interpersonal skills are needed for geospatial market development, as well as models to describe the types of workers needed in the geospatial information technology industry, increase employee recruitment and selection, manage employee performance, design geospatial information technology training and education programs [9]. Based on this in advance and with the increasingly urgent need for geospatial resources, it is necessary to develop a real time and easily available geospatial resource data processing facility, it is necessary to formulate to define the level of human resource competency.…”
Section: Introductionmentioning
confidence: 99%